Duration of Severe Acute Respiratory Syndrome Coronavirus 2 Natural Immunity and Protection Against the Delta Variant: A Retrospective Cohort Study - Kim, Priscilla; Gordon, Steven M; Sheehan, Megan M; Rothberg, Michael B (Clinical infectious diseases, 2022)
Infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been shown to be highly protective against reinfection and symptomatic disease. However, effectiveness against the Delta variant and duration of natural immunity remain unknown.BACKGROUNDInfection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been shown to be highly protective against reinfection and symptomatic disease. However, effectiveness against the Delta variant and duration of natural immunity remain unknown.This retrospective cohort study included 325 157 patients tested for SARS-CoV-2 via polymerase chain reaction (PCR) from 9 March 2020 to 31 December 2020 (Delta variant analysis) and 152 656 patients tested from 9 March 2020 to 30 August 2020 (long-term effectiveness analysis) with subsequent testing through 9 September 2021. The primary outcome was reinfection, defined as a positive PCR test >90 days after the initial positive test.METHODSThis retrospective cohort study included 325 157 patients tested for SARS-CoV-2 via polymerase chain reaction (PCR) from 9 March 2020 to 31 December 2020 (Delta variant analysis) and 152 656 patients tested from 9 March 2020 to 30 August 2020 (long-term effectiveness analysis) with subsequent testing through 9 September 2021. The primary outcome was reinfection, defined as a positive PCR test >90 days after the initial positive test.Among 325 157 patients tested before 31 December 2020, 50 327 (15.5%) tested positive. After 1 July 2021 (Delta dominant period), 40 (0.08%) initially positive and 1494 (0.5%) initially negative patients tested positive. Protection of prior infection against reinfection with Delta was 85.4% (95% confidence interval [CI], 80.0-89.3). For the long-term effectiveness analysis, among 152 656 patients tested before 30 August 2020, 11 186 (7.3%) tested positive. After at least 90 days, 81 (0.7%) initially positive and 7167 (5.1%) initially negative patients tested positive. Overall protection of previous infection was 85.7% (95% CI, 82.2-88.5) and lasted up to 13 months. Patients aged >65 years had slightly lower protection.RESULTSAmong 325 157 patients tested before 31 December 2020, 50 327 (15.5%) tested positive. After 1 July 2021 (Delta dominant period), 40 (0.08%) initially positive and 1494 (0.5%) initially negative patients tested positive. Protection of prior infection against reinfection with Delta was 85.4% (95% confidence interval [CI], 80.0-89.3). For the long-term effectiveness analysis, among 152 656 patients tested before 30 August 2020, 11 186 (7.3%) tested positive. After at least 90 days, 81 (0.7%) initially positive and 7167 (5.1%) initially negative patients tested positive. Overall protection of previous infection was 85.7% (95% CI, 82.2-88.5) and lasted up to 13 months. Patients aged >65 years had slightly lower protection.SARS-CoV-2 infection is highly protective against reinfection with Delta. Immunity from prior infection lasts at least 13 months. Countries facing vaccine shortages should consider delaying vaccinations for previously infected patients to increase access.CONCLUSIONSSARS-CoV-2 infection is highly protective against reinfection with Delta. Immunity from prior infection lasts at least 13 months. Countries facing vaccine shortages should consider delaying vaccinations for previously infected patients to increase access.